The fission yeast rad22 gene, having a function in mating-type switching and repair of DNA damages, encodes a protein homolog to Rad52 of Saccharomyces cerevisiae. - Ostermann, K (1993)
The gene rad22 of the fission yeast Schizosaccharomyces pombe has a function in DNA repair and mating-type switching. We have cloned the rad22 gene from a genomic gene bank by functional complementation of the switching defect. An open reading frame coding for a putative protein of 469 amino acids was found by sequence analyses. The rad22 gene contains no intron. A region of 126 amino acids in the N-terminal half of the Rad22 protein has significant homologies (56% identity and 36% similarity) to the Rad52 protein of Saccharomyces cerevisiae. A rad22 disruption strain was constructed which seems to be inviable in a homothallic background. Southern blot analyses have shown that the rad22-67 mutant frequently gives rise to deletions in the mating-type region. These data indicate that the Rad22 protein has a function in the repair of DNA double-strand breaks.